2011
DOI: 10.1590/s0100-84042011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Mating system in Myracrodruon urundeuva (Anarcadiaceae): implications for conservation genetics

Abstract: -Mating system in Myracrodruon urundeuva (Anarcadiaceae): implications for conservation genetics. The aims of this study were to investigate the mating system of a fragmented population of the dioecious tropical tree Myracrodruon urundeuva Allemão, using five microsatellite loci and the mixed mating and correlated mating models. The study was conducted in the Estação Ecológica de Paulo de Farias (436 ha), where the population occupies about 142 ha. The mating system was estimated using 514 open-pollinated offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
1
Order By: Relevance
“…The medicinal plant M. urundeuva has an important ecological role in the caatinga and brejo de altitude ecosystems, where this species contribute with native pollinators (Gaino et al 2011); however, the diversity of endophytic fungi from this species has not been studied in these two ecosystems, to the best of our knowledge, this study is the first report of endophytes and their biotechnological potential to produce L-asparaginase. Although some surveys (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…The medicinal plant M. urundeuva has an important ecological role in the caatinga and brejo de altitude ecosystems, where this species contribute with native pollinators (Gaino et al 2011); however, the diversity of endophytic fungi from this species has not been studied in these two ecosystems, to the best of our knowledge, this study is the first report of endophytes and their biotechnological potential to produce L-asparaginase. Although some surveys (e.g.…”
Section: Discussionmentioning
confidence: 94%
“…& M.F. Allemão), or "aroeira" (Anarcadiaceae), is a dioecious species [2,3] with high wood quality and medicinal properties [4], but threatened of extinction [5] due to strong forest fragmentation of their biomes of occurrence. Native of South America, it occurs in Brazil, Bolivia, Paraguay and Argentina [6].…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular markers in population genetic studies of tree species has been shown to be effective. In M. urundeuva, previous studies were performed using isoenzyme markers [7,8], RAPD and cpDNA [9,10], AFLP [11,12] and more recently by microsatellite markers [1,3,[13][14][15]. In these last studies, nine microsatellite loci developed by Caetano et al [13] were used in the analysis of populations of M. urundeuva only from Paraguay and Argentina.…”
Section: Introductionmentioning
confidence: 99%
“…Through these results, it is possible to plan that seed collection be performed in the most genetically distant mother trees, resulting in seeds with greater genetic variability, since the more divergent the parents, the greater the diversity of their progenies (Manfio et al 2012). In addition to this information, it is also necessary to distinguish individuals by sex for seed collection, taking into account the species M. urundeuva is predominantly dioecious (Gaino et al 2011). Collecting seeds taking into account the genetic diversity of species is essential to avoid future problems such as associated anomalies (anatomical deformities), dwarfism, physiological disorders, albinism or even mortality due to low weather resistance or pest attacks and other pathological agents, besides ensuring the preservation of the different alleles present in the species.…”
Section: Resultsmentioning
confidence: 99%